Formation Rules of Harmful Gas Products of Flame Colour Agents of Fireworks - Xiang Yang, Liu; Jian Xing, Gao; Yong, Chen; Bang Xing, Xu; Rui Zhang, Yang (Asian Journal of Chemistry, 2013)
The influence of fireworks bring to the environment can't be neglected. By calculating and simulation experiment with the principle of free energy minimum, this study reports the formation rules of harmful by products of colouring flame of fireworks with the results as follows: the major harmful gas in the combustion by product of colouring flame is carbon monoxide. After analyzing, oxygen negative balance in the composition of colouring agent is found to be the main reason for the formation of carbon monoxide and raise the oxygen balance in the composition could reduce the formation of carbon monoxide.